THE EFFECT OF PORE DISTRIBUTION IN HISTORIC MASONRY ON THE GROUTING METHOD AND GROUTING MIX SELECTION - Jiří Witzany; Radek Zigler; Klára Kroftová; Tomáš Čejka; Jan Kubát; Milan Holický; Jiří Karas (Civil Engineering Journal, 2018)
The NAKI II DG16P02M055 research project incorporates extensive experimental and theoretical research into the effect of grouting on the physical and mechanical characteristics of brick, stone and mixed masonry. The focus of the research is on the verification of particularly the reinforcing effect of selected grouting agents based on hydraulic lime (nanolime), resins and silicates. Selected materials are used for the monitoring of the effect of grouting on changes in the porosity, pore distribution, absorption capacity as compared to ungrouted masonry, and the reinforcing effect of grouting on historic brick, sandy marlstone, sandstone, trachyte, limestone and mixed masonry with a lime binder for different types of grouting agents as compared to ungrouted masonry.